Wear-resistant anti-aging organic silicon modified asphalt for fog sealing layer and preparation method of wear-resistant anti-aging organic silicon modified asphalt
By using wear-resistant and anti-aging silicone modified asphalt, combined with catalytic cracked oil slurry and modified graphene oxide and other raw materials, the problem of insufficient bonding strength and permeability of the fog sealing material is solved, and the wear resistance of the material is improved Performance and service life achieve long-lasting and durable anti-seepage effect.
Patent Information
- Application Number
- CN202410293077.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-14
- Publication Date
- 2025-01-07
AI Technical Summary
The existing fog sealing layer materials have problems such as low bond strength, poor permeability, insufficient wear resistance, easy layering, and unlimited long-term durability and anti-seepage, and the traffic closure time is long after construction.
Wear-resistant and anti-aging silicone modified asphalt is used to form high bond strength and good permeability by reasonably proportioning petroleum asphalt, catalytic cracked oil slurry, silicone polymer resin, modified graphene oxide, suspension agent and other raw materials. Materials with properties and wear resistance, and improve emulsion dispersion and film formation performance through sonication and high-speed shearing techniques.
It significantly improves the bonding strength, permeability and wear resistance of the fog seal layer, extends the service life of the material, shortens the traffic recovery time after construction, and achieves a long-term and durable anti-seepage effect.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure FDA0004741337920000011
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of road engineering, and in particular to a wear-resistant and anti-aging type organosilicon modified asphalt for a fog seal layer and a preparation method thereof. Background Art
[0002] The fog seal is a kind of preventive maintenance material, which is a special mobile emulsion (usually emulsified asphalt) with closed pores and regeneration function sprayed on the road surface. There are generally three ways to convert solid asphalt into a liquid flow state: (1) heating it to flow; (2) diluting asphalt with solvents; (3) preparing emulsified asphalt. Based on this, there are two main maintenance mechanisms of the fog seal on the road surface. One is to use emulsified asphalt to spray on the road surface to form a short-term protective layer, and the other is to use reducing agent materials to spray on the road surface to improve the problem of asphalt hardening due to aging.
[0003] The principle of the reducing agent fog seal layer on pavement regeneration is, on the one hand, to physically isolate the asphalt pavement to prevent the pavement aggregate from falling off due to insufficient adhesion and the infiltration of surface water; on the other hand, the regenerated components in the fog seal layer penetrate into the asphalt according to the principle of like dissolves like, compensate for the conversion of saturated and aromatic components during the asphalt aging process, balance the ratio of the four components, and thus improve the penetration, softening point, ductility and other properties of the aged asphalt.
[0004] At present, the fog seal used in road construction often has the following problems: 1. Diluted asphalt is mostly matrix asphalt, which has poor permeability to the original asphalt base surface and low bonding strength. 2. The demulsification / volatization time of the fog seal material is slow, so it takes a long time to open traffic after construction. 3. The material composition is simple and cannot achieve compensation after the asphalt film of the road surface is polished. The thickness is thin and cannot achieve "long-term and durable anti-seepage". 4. The mother liquid is unstable in storage and unevenly dispersed, which is prone to stratification, flocculation, segregation and other phenomena.
[0005] Therefore, it is imperative to develop a fog sealing material with high bonding strength, strong permeability, waterproof and anti-fouling, abrasion resistance and UV resistance. Summary of the invention
[0006] The technical problem to be solved by the present invention is to provide a wear-resistant and anti-aging type silicone modified asphalt for fog seal layer and its preparation method, so as to improve the regeneration and penetration ability of fog seal layer materials, increase the adhesion and wear resistance of protective film, and extend the service life of fog seal layer materials.
[0007] The technical problem to be solved by the present invention is achieved by adopting the following technical solutions:
[0008] The first object of the present invention is to provide a wear-resistant and anti-aging type organosilicon modified asphalt, comprising the following raw materials in parts by weight:
[0009]
[0010] In a further technical solution, the petroleum asphalt is Esso 90# petroleum asphalt or 110# petroleum asphalt.
[0011] Catalytic cracking slurry, referred to as FCC slurry, is a by-product of the catalytic cracking unit of the refinery. FCC slurry has a high aromatic content and strong penetration ability.
[0012] In a further technical solution, the FCC slurry oil contains 30-40% by weight of saturated hydrocarbons and 50-55% by weight of aromatic hydrocarbons.
[0013] In a further technical solution, the silicone polymer resin composition is a mixture of silicone resin, thermosetting acrylic resin, hydrogenated rosin and wear-resistant additive; preferably, the mass ratio of the silicone resin, thermosetting acrylic resin, hydrogenated rosin and wear-resistant additive is 4:4:1:2.
[0014] In a further technical solution, the wear-resistant additive is one or more of dimethylsiloxane and silicone-modified polysiloxane.
[0015] In a further technical solution, the modified graphene oxide is made of triethanolamine and graphene oxide, and the mass ratio of triethanolamine to graphene oxide is 1:48.
[0016] In a further technical solution, the initiator is one or more of hexadecyltrimethylammonium chloride, benzoyl peroxide, and hydrogen peroxide. Among them, hexadecyltrimethylammonium chloride is used as a phase transfer catalyst and has a certain softening effect, and is used as a UV absorber and a modification of graphene oxide.
[0017] In a further technical solution, the organic stabilizer is a mixture of styrene-butadiene rubber, hydrochloric acid, turpentine, organotin and alkylphenol polyoxyethylene ether; preferably, the mass ratio of the styrene-butadiene rubber, hydrochloric acid, turpentine, organotin and alkylphenol polyoxyethylene ether is 66:4:4:3:23, wherein the hydrochloric acid is a dilute hydrochloric acid with a mass fraction of 1%. The specific preparation method is as follows:
[0018] A. Add styrene-butadiene rubber, turpentine and organotin into deionized water, shear at high speed, and then ultrasonically treat to obtain an emulsion;
[0019] B. Add alkylphenol polyoxyethylene ether into the above emulsion, add hydrochloric acid dropwise, stir evenly, and obtain an organic stabilizer.
[0020] In a further technical solution, the suspending agent is one or more of diatomaceous earth, kaolin, magnesium aluminosilicate, and bentonite.
[0021] In a further technical solution, the ultraviolet absorber is a benzophenone ultraviolet absorber, selected from one or more of 2,4-dihydroxybenzophenone, 2-hydroxy-4-methoxybenzophenone, and 2-hydroxy-4-n-octyloxybenzophenone.
[0022] The second object of the present invention is to provide a method for preparing the wear-resistant and aging-resistant organosilicon-modified asphalt, comprising the following steps:
[0023] (1) Under nitrogen protection, reacting an organosilicon polymer composition, FCC oil slurry, an organic stabilizer and an initiator to form a graft copolymer to obtain a prepolymer emulsion, ultrasonically treating the prepolymer emulsion, and cooling the prepolymer emulsion to room temperature;
[0024] (2) Under nitrogen protection, the ultrasonically treated prepolymer emulsion is heated to 120-140° C., petroleum asphalt and modified graphene oxide are added, and high-speed shearing is performed, and then the temperature is reduced to 100-120° C., a suspending agent and an ultraviolet absorber are added, and high-speed shearing is performed to obtain a wear-resistant and anti-aging type silicone modified asphalt.
[0025] Under the action of the initiator, the FCC oil slurry and the organic stabilizer are used to graft and modify the organosilicon polymer composition.
[0026] In some specific embodiments, the grafting reaction temperature is 60-85°C.
[0027] In some specific embodiments, the frequency of the ultrasonic treatment is 50-60 Hz, and the power is 400-500 W. The purpose of the ultrasonic treatment is to form a high-concentration, low-molecular-size emulsion dispersion and improve the emulsification quality.
[0028] The third object of the present invention is to provide the use of the wear-resistant and aging-resistant organosilicon-modified asphalt in the preparation of a pavement fog seal layer.
[0029] The beneficial effects of the present invention are:
[0030] 1. The organosilicon polymer resin composition of the present invention is prepared by rationally mixing organosilicon resin, thermosetting acrylic resin, hydrogenated rosin and wear-resistant additive, so as to ensure that the thin layer after volatilization has good resistance to shear damage. The molecular structure of organosilicon resin is cross-linked by -Si-O-Si- to form a hydrophobic main chain, and the side chains are methyl and ethoxy groups, which are non-polar groups. The side chains surround the main chain and thus have strong "hydrophobicity", which can improve the water stability of the system. Compared with epoxy resin, it has the advantages of good affinity, fast drying and high firmness, and improves the wear resistance and adhesion of silicon-modified asphalt after film formation; thermosetting acrylic resin is used as an auxiliary film-forming substance, and the addition thereof can improve the flexibility and scratch resistance of the coating; hydrogenated rosin contains rosin acid, and the rosin acid molecular structure contains a large number of double bonds or carboxyl functional groups, which form hydrogen bonds with the organosilicon gel in the system, thereby enhancing the cohesive strength of the system and improving the adhesive strength of the system.
[0031] 2. The present invention utilizes the intermolecular force between the light aromatic components in the FCC oil slurry and the resin in the organosilicon polymer resin to break and disperse the resin macromolecular chain to form an organosilicon group, thereby avoiding the problem of poor compatibility caused by the large difference in the chemical properties of the organosilicon material and asphalt; the organosilicon group reacts with organotin to generate an organosilicon tin compound, thereby improving the weather resistance, high temperature resistance and corrosion resistance of the material; the organosilicon polar group forms a hydrogen bond with the double bond or carboxyl functional group in the hydrogenated rosin, thereby improving the wear resistance and adhesion of the material.
[0032] 3. The prepolymer-modified petroleum asphalt used in the present invention contains abundant aromatic light components and hydrogen bond combinations, which can have good dispersion, infiltration and penetration effects on the asphalt base surface. By penetrating the base, the fog seal layer and the original asphalt pavement can form a unified whole, thereby enhancing the bonding strength of the material.
[0033] 4. The modified graphene oxide used in the present invention can be dispersed in the unsaturated resin matrix, so that the organic silicone gel can completely wrap it, thereby avoiding the problem of secondary agglomeration during storage; at the same time, the large specific surface area and wrinkled structure of the modified graphene oxide itself ensure the maximum contact area with the organic silicone gel, which is beneficial to the transfer of stress after film formation from the matrix organic silicone resin to the modified graphene, so that the mechanical properties of the film are improved.
[0034] 5. The main component of the suspending agent used in the present invention is layered silicate minerals. The special lamellar structure can slow down the movement of oxygen in the asphalt, thereby reducing the thermal oxygen aging of the asphalt. At the same time, the suspending agent can also stabilize the light components in the asphalt, has a certain peptizing effect, and forms a stable colloidal structure with the asphalt, thereby improving the thermal stability and aging resistance of the system. DETAILED DESCRIPTION
[0035] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further described below in conjunction with specific embodiments.
[0036] The raw materials in the following examples and comparative examples are described:
[0037] The FCC slurry oil was purchased from Sinopec Guangdong Branch, with aromatic hydrocarbons accounting for 52% and saturated hydrocarbons accounting for 34%.
[0038] The silicone polymer resin composition is a mixture of silicone resin, thermosetting acrylic resin, hydrogenated rosin and wear-resistant additive in a mass ratio of 4:4:1:2, wherein the wear-resistant additive is a mixture of dimethylsiloxane and silicone-modified polysiloxane in a mass ratio of 2:1. The dimethylsiloxane is Silsurf J208 from Stai Chemical; the silicone-modified polysiloxane is TEGOPREN 7008 from Degussa Evonik; the silicone resin is XIAMETER RSN-0805 resin from Dow Corning; the thermosetting acrylic resin is KN2566F from Kolison; and the hydrogenated rosin is Foralyn E-partially hydrogenated rosin from Eastman Natural Resins.
[0039] Preparation of modified graphene oxide: A triethanolamine and graphene oxide aqueous solution (concentration of 5 mg / mL) with a mass ratio of 1:48 was ultrasonically dispersed (frequency of 50 Hz, power of 500 W, time of 20 min), then the temperature was raised to 60 ° C and ball milled for 10 min, followed by centrifugation at 100 r / min for 15 min, and finally dried at 55 ° C for 45 min to obtain modified graphene oxide.
[0040] The initiator is a mixture of hexadecyltrimethylammonium chloride, benzoyl peroxide and hydrogen peroxide in a mass ratio of 2:1:1.
[0041] The organic stabilizer is a mixture of styrene-butadiene rubber, hydrochloric acid, turpentine, organotin and alkylphenol polyoxyethylene ether in a mass ratio of 66:4:4:3:23, wherein the hydrochloric acid is a dilute hydrochloric acid with a mass fraction of 1%. The preparation method of the organic stabilizer is as follows: A. Add styrene-butadiene rubber, turpentine and organotin into deionized water, shear at 3000rpm for 30min, and then ultrasonically treat at a frequency of 50Hz and a power of 500W for 30min to obtain an emulsion; B. Add the alkylphenol polyoxyethylene ether into the above emulsion, drop hydrochloric acid, and stir at 2000rpm for 15min to obtain the organic stabilizer. Among them, styrene-butadiene rubber is purchased from Sinopec Fushun Petrochemical; turpentine is purchased from Merck Sigma-Aldrich, CAS No.: 8006-64-2; organotin is the organotin catalyst CUCAT-S9 of Guangzhou Yourun Synthetic Materials Co., Ltd.; and alkylphenol polyoxyethylene ether is Kaiyin Chemical OP-10.
[0042] The suspension agent is a mixture of diatomaceous earth and kaolin in a mass ratio of 2:1, wherein the diatomaceous earth and kaolin are purchased from Qingdao Shengtai Silicon Industry Co., Ltd.
[0043] The ultraviolet absorber is 2-hydroxy-4-methoxybenzophenone.
[0044] Example 1
[0045] Preparation of silicone modified asphalt:
[0046] 100 parts of 110# Esso asphalt, 20 parts of FCC slurry oil, 40 parts of organosilicon polymer resin composition, 12 parts of modified graphene oxide, 6 parts of initiator, 15 parts of organic stabilizer, 4 parts of suspending agent, and 2 parts of ultraviolet absorber.
[0047] The specific preparation process includes the following steps:
[0048] (1) Under nitrogen protection, the organosilicon polymer composition, FCC oil slurry, organic stabilizer and initiator were reacted at 80° C. for 70 min to obtain a prepolymer emulsion, which was ultrasonically treated (frequency 50 Hz, power 500 W, time 20 min), and cooled to room temperature.
[0049] (2) Under nitrogen protection, the prepolymer emulsion after ultrasonic treatment was heated to 140°C, petroleum asphalt and modified graphene oxide were added, and shearing was carried out at 2000 rpm for 30 min. Then, the temperature was cooled to 100°C, a suspending agent and an ultraviolet absorber were added, and high-speed shearing was carried out at 4000 rpm for 1 h to obtain wear-resistant and anti-aging silicone modified asphalt.
[0050] Example 2
[0051] Preparation of silicone modified asphalt:
[0052] 100 parts of 110# Esso asphalt, 23 parts of FCC slurry oil, 45 parts of organosilicon polymer resin composition, 10 parts of modified graphene oxide, 5 parts of initiator, 12 parts of organic stabilizer, 6 parts of suspending agent, and 2 parts of ultraviolet absorber.
[0053] The specific preparation process is the same as that in Example 1.
[0054] Example 3
[0055] Preparation of silicone modified asphalt:
[0056] 100 parts of 110# Esso asphalt, 24 parts of FCC slurry oil, 42 parts of organosilicon polymer resin composition, 10 parts of modified graphene oxide, 4 parts of initiator, 11 parts of organic stabilizer, 6 parts of suspending agent, and 2 parts of ultraviolet absorber.
[0057] The specific preparation process is the same as that in Example 1.
[0058] Example 4
[0059] Preparation of silicone modified asphalt:
[0060] 100 parts of 110# Esso asphalt, 21 parts of FCC slurry oil, 50 parts of organosilicon polymer resin composition, 12 parts of modified graphene oxide, 6 parts of initiator, 14 parts of organic stabilizer, 4 parts of suspending agent, and 2 parts of ultraviolet absorber.
[0061] The specific preparation process is the same as that in Example 1.
[0062] Example 5
[0063] Preparation of silicone modified asphalt:
[0064] 100 parts of 110# Esso asphalt, 25 parts of FCC slurry oil, 50 parts of organosilicon polymer resin composition, 6 parts of modified graphene oxide, 6 parts of initiator, 10 parts of organic stabilizer, 4 parts of suspending agent, and 1 part of ultraviolet absorber.
[0065] The specific preparation process is the same as that in Example 1.
[0066] Comparative Example 1
[0067] The difference between Comparative Example 1 and Example 5 is that FCC oil slurry is not added to modify the organosilicon polymer resin composition.
[0068] Comparative Example 2
[0069] The difference between Comparative Example 2 and Example 5 is that no organic stabilizer is added to modify the organosilicon polymer resin composition.
[0070] Comparative Example 3
[0071] The preparation process of 5% SBR modified asphalt is as follows:
[0072] 100 parts of 110# Esso asphalt were heated to 130°C, then 5 parts of SBR resin were added, heated to 140°C and stirred for 50 minutes, and placed in a constant temperature oven at 125°C for 3 hours to obtain 5% SBR modified asphalt.
[0073] The modified asphalt prepared in the above Examples 1-5 and Comparative Examples 1-3 was subjected to performance tests, and the test results are shown in Table 1.
[0074] The bonding strength with the base surface is tested in accordance with Appendix B of CJJ139-2010 "Technical Code for Urban Bridge Deck Waterproofing Engineering".
[0075] The curing time is tested in accordance with GB / T16777-2008 "Test methods for building waterproof coatings".
[0076] The impermeability is tested in accordance with T0971-2008 "Test method for water permeability coefficient of asphalt pavement".
[0077] The wear resistance is tested in accordance with GB / T 1768 “Determination of wear resistance of paints, varnishes and paint films”, and the test conditions are: 750g, 500rpm.
[0078] The UV resistance test is to evenly spread the sample on a marble slab, put it into a UV aging box (UVA 340 lamp, 8h illumination, 4h condensation, irradiation intensity 0.76W, room temperature 60℃ for illumination, 50℃ for darkness, no cycle), calculate the radiation amount based on the irradiation time, and characterize it based on the rate of change of the material's tensile strength after UV irradiation.
[0079] Table 1 Performance test results of modified asphalt
[0080]
[0081] As can be seen from Table 1, compared with Comparative Examples 1-3, the bond strength of the organosilicon modified asphalt prepared in Examples 1-5 is not less than 1.0 MPa, the curing time is less than 3 hours, the anti-permeability improvement rate is greater than 90%, the wear resistance is less than 15 mg, and the UV resistance reduction rate is less than 50%. Therefore, the organosilicon modified asphalt prepared by the present invention has excellent performance as a fog seal material.
[0082] In summary, the organosilicon-modified asphalt for the fog seal layer prepared by the present invention has good high and low temperature performance and molding strength, and has strong adaptability to the construction environment, is waterproof and oil-resistant, wear-resistant, acid-resistant and alkali-resistant, and has good application value and economic benefits.
[0083] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A wear-resistant and anti-aging organosilicon modified asphalt, characterized in that: The invention comprises the following raw materials in parts by weight:
2. The wear-resistant and aging-resistant organosilicon-modified asphalt according to claim 1 is characterized in that: The petroleum asphalt is Esso 90# petroleum asphalt or 110# petroleum asphalt; the FCC oil slurry contains 30-40% by weight of saturated hydrocarbons and 50-55% by weight of aromatic hydrocarbons.
3. The wear-resistant and aging-resistant organosilicon-modified asphalt according to claim 1 is characterized in that: The organosilicon polymer resin composition is a mixture of organosilicon resin, thermosetting acrylic resin, hydrogenated rosin and wear-resistant additive; preferably, the mass ratio of the organosilicon resin, thermosetting acrylic resin, hydrogenated rosin and wear-resistant additive is 4:4:1:2; preferably, the wear-resistant additive is one or more of dimethylsiloxane and silicone-modified polysiloxane.
4. The wear-resistant and aging-resistant organosilicon-modified asphalt according to claim 1, characterized in that: The modified graphene oxide is made of triethanolamine and graphene oxide, and the mass ratio of triethanolamine to graphene oxide is 1:
48.
5. The wear-resistant and aging-resistant organosilicon-modified asphalt according to claim 1 is characterized in that: The initiator is one or more of hexadecyltrimethylammonium chloride, benzoyl peroxide and hydrogen peroxide.
6. The wear-resistant and aging-resistant organosilicon-modified asphalt according to claim 1, characterized in that: The organic stabilizer is a mixture of styrene-butadiene rubber, hydrochloric acid, turpentine, organotin and alkylphenol polyoxyethylene ether; preferably, the mass ratio of the styrene-butadiene rubber, hydrochloric acid, turpentine, organotin and alkylphenol polyoxyethylene ether is 66:4:4:3:23, wherein the hydrochloric acid is a dilute hydrochloric acid with a mass fraction of 1%.
7. The wear-resistant and aging-resistant organosilicon-modified asphalt according to claim 1, characterized in that: The suspending agent is one or more of diatomaceous earth, kaolin, magnesium aluminosilicate and bentonite.
8. The wear-resistant and aging-resistant organosilicon-modified asphalt according to claim 1, characterized in that: The ultraviolet absorber is a benzophenone ultraviolet absorber, which is selected from one or more of 2,4-dihydroxybenzophenone, 2-hydroxy-4-methoxybenzophenone, and 2-hydroxy-4-n-octyloxybenzophenone.
9. The method for preparing the wear-resistant and aging-resistant organosilicon-modified asphalt according to any one of claims 1 to 8, characterized in that: The following steps are involved: (1) Under nitrogen protection, reacting an organosilicon polymer composition, FCC oil slurry, and an organic stabilizer with an initiator to form a graft copolymer to obtain a prepolymer emulsion, ultrasonically treating the prepolymer emulsion, and cooling the prepolymer emulsion to room temperature; (2) Under nitrogen protection, the ultrasonically treated prepolymer emulsion is heated to 120-140° C., petroleum asphalt and modified graphene oxide are added, and high-speed shearing is performed, and then the temperature is reduced to 100-120° C., a suspending agent and an ultraviolet absorber are added, and high-speed shearing is performed to obtain a wear-resistant and anti-aging type silicone modified asphalt.
10. Use of the wear-resistant and aging-resistant organosilicon-modified asphalt according to any one of claims 1 to 8 in preparing a pavement fog seal layer.
Citation Information
Cited By
Waterproof material for house repair and preparation method thereof
CN121801340A